The lion tamer - Hansen, Sarah, author; Doenges, Judy, advisor; Becker, Leslee, committee member; Alexander, Ruth, committee member (Colorado State University. Libraries, 2016)
The Lion Tamer is a novel set in an early 20th century Midwest American circus, following the stories of two women whose lives become entangled when they are both involved in a murder. The novel centers mainly on a young woman, Mae, who runs away after the death of her parents and joins the circus. She connects with a young lion cub, and consequently works her way up to become one of the world's first female lion tamers. She meets Ziggy, a Painted Lady who murders her husband, and together, their paths spiral into deceit, blackmail, and abuse. The novel's main concern is power and autonomy, especially for women at the turn of the century, and what sacrifices each character makes to gain both.